The relative importance of predictive factors for single first-generation EGFR-TKI use for more than 5 years in patients with advanced non-small cell lung cancer: Taiwan multicenter TIPS-5 study. (May 2021) - Huang, Yen-Hsiang; Hung, Jen-Yu; Ko, How-Wen; Su, Po-Lan; Lai, Chun-Liang; Chang, Huang-Chih; Hsia, Te-Chun; Lin, Sheng-Hao; Wu, Kuan-Li; Yang, Cheng-Ta; Su, Wu-Chou; Chu, Yi-Chun; et al.
Background: The relative importance of predictive factors for advanced non-small cell lung cancer (NSCLC) patients on epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) treatment remains unclear. Materials and methods: We retrospectively enrolled advanced NSCLC patients with single first-generation EGFR-TKI treatment for ⩾5 years (Y) in Taiwan. Clinical data was collected and compared with those of another cohort with single first-line EGFR-TKI treatment for <5 Y. Plasma cell-free DNA (cfDNA) samples were collected from patient subsets, pre- and post-TKI, in the >5 Y group. Results: Overall, 128 and 278 patients were enrolled in the ⩾5 Y and <5 Y groups, respectively. Significant factors in the multivariate analysis of patients' characteristics including Eastern Cooperative Oncology Group performance status 0–1, postoperative recurrence, without brain metastasis, oligometastasis (each score of 2), female sex, erlotinib use, and without bone metastasis (each score of 1), were incorporated into a risk scoring system. The area under the receiver operating characteristic curve was 0.82 [95% confidence interval (CI): 0.78–0.86]. Of the plasma cfDNA samples from 33 patients in the ⩾5 Y group, only 1 had a T790M in 25 patients without progressive disease. In 27 patients with single agent use for ⩾96 months, 22 (81.5%) received local treatment (surgery or radiotherapy) for the primary lung tumor before and during TKI treatment. Conclusion: For NSCLC patients with single first-generation EGFR-TKI use for ⩾5 Y, factors with different relative importance exist and the risk-scoring model is feasible with modest accuracy. The role of local treatment for primary tumors in patients with long-term TKI use requires further investigation.